2016
DOI: 10.3221/igf-esis.38.06
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial fatigue assessment of crankshafts by local stress and critical plane approach

Abstract: ABSTRACT. For multiaxially-loaded parts several stress-based fatigue assessment concepts are applicable mostly taking uniaxial test results as basis. These approaches work well in case of proportional loading states, but on contrary, for non-proportional stress conditions, implying a change of the principal stress direction, deviations in the fatigue life estimation may occur. The aim of this study is to evaluate the cyclic multiaxial material behavior experimentally and to proof the applicability of stress-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Those pipes receive multiaxial loading by movement of internal fluid [1]. However, most of the fatigue data which are used for those strength designs are obtained by uniaxial loading tests, and there is limited data under multiaxial loading [2][3]. The equivalent stress based on von Mises is generally used in the design for structures under multiaxial loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those pipes receive multiaxial loading by movement of internal fluid [1]. However, most of the fatigue data which are used for those strength designs are obtained by uniaxial loading tests, and there is limited data under multiaxial loading [2][3]. The equivalent stress based on von Mises is generally used in the design for structures under multiaxial loading.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent stress based on von Mises is generally used in the design for structures under multiaxial loading. In recent literatures of multiaxial fatigue, it is reported that fatigue life evaluated by the Mises' equivalent stress is overestimated [2][3][4][5][6][7][8][9] and the degree depends on loading path [10][11]. In the multiaxial fatigue under non-proportional loading in which directions of principal stress and strain are changed in a cycle, it has been reported that fatigue lives are reduced accompanying additional hardening which depends on both loading path and material.…”
Section: Introductionmentioning
confidence: 99%